Implikasi Konsep Derivatif Dalam Memaksimalkan Keuntungan (Studi Kelayakan pada Toko Kue Ulfa, Medan Sunggal) - Syahrul Amsari; Nabil Shawab; Windu Anggara; Isnaini Harahap (UNIVERSITAS MUHAMMADIYAH SUMATERA UTARA, 2023)
The concept of the derivative is one of the mathematical approaches used to carry out maximum profit analysis. This research aims to carry out an analysis related to the implications of the derivative concept in maximizing profits which was carried out at Ulfa Cake Shop, a home-based business at Jalan Amal No 13, Medan Sunggal District, Medan City which was just started. In this research using problem research procedures with a qualitative approach. Observations made at Ulfa Cake Shop show that business owners are still having difficulty getting optimal profits due to changes in the selling price of several variations of the products being sold. The results of this research show that Ulfa Cake Shop is still not able to achieve optimal profits because not all product variations sold reach the maximum sales level when compared to sales in November and December 2022, even though the results of the second derivative analysis are negative.